Plant exploration for native hop in the American southwest - Smith, J.M.=700 1 Oliphant, J.M.; Hummer, K.E.
(En, Fr, Es)
Ilus., 15 ref.
Keywords: HUMULUS LUPULUS; RECURSOS GENETICOS; GERMOPLASMA; ITALIA